Bioethics in the Ruins. Issue 3 (21st May 2020) - Porter, Allen
Abstract: In The Foundations of Bioethics (1986, 1996), former senior editor of The Journal of Medicine and Philosophy H. Tristram Engelhardt, Jr. (1941–2018) radically reassessed the nature and scope of bioethics, as well as the possibilities for this still-young field that he helped found, in light of the prevailing sociohistorical context, which he argued had been inadequately considered by bioethicists. This issue of The Journal of Medicine and Philosophy provides a snapshot of how bioethics is developing in the wake of Engelhardt's critique. Topics covered include the relation between rule of law and US healthcare policy, the relation between autonomy and consent, the role of rights in bioethical discourse, the debate between naturalism and normativism in the theory of disease, and the question of when human individuals begin to exist. Although no single theme explicitly unites them, the papers in this issue were produced within and are fruitfully read in terms of what Engelhardt influentially characterized as a morally pluralistic postmodernity subsisting amidst the ruins of tradition. In the conclusion, I introduce a further wrinkle into this Engelhardtian picture—namely, the looming danger of a more general epistemological pluralism effected by new technologies like Deepfakes.